1983
DOI: 10.1039/p19830002479
|View full text |Cite
|
Sign up to set email alerts
|

Photolysis of alkoxyacetic acids in the presence of mercury(II) oxide and lodine

Abstract: Homolytic decarboxylation of a series of alkoxyacetic acids has furnished alkoxyalkyl alkoxyacetates when no substituents were present at the 2-position. Electron donating and withdrawing 2-substituents, with the exception of trichloromethyl, afforded products due to fragmentation of the alkoxyacetic acids. The reaction pathway is rationalised on the basis of the reactivity of the alkoxyalkyl iodide intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The diazo precursor is expected to be readily accessible from the corresponding β-ketoester, which can be obtained from acid V after Dieckmann condensation of the activated acid with methyl 2-lithioacetate. Finally, acid V can be conceived as being generated by an enolate [3,3]-sigmatropic rearrangement , of VI [R 1 = Bn and R 2 = p -methoxybenzyl (PMB)], which in turn can be prepared, in one step, from known ( E )-4-(benzyloxy)but-2-en-1-ol and p -methoxybenzyloxyacetic acid 1 …”
Section: Resultsmentioning
confidence: 99%
“…The diazo precursor is expected to be readily accessible from the corresponding β-ketoester, which can be obtained from acid V after Dieckmann condensation of the activated acid with methyl 2-lithioacetate. Finally, acid V can be conceived as being generated by an enolate [3,3]-sigmatropic rearrangement , of VI [R 1 = Bn and R 2 = p -methoxybenzyl (PMB)], which in turn can be prepared, in one step, from known ( E )-4-(benzyloxy)but-2-en-1-ol and p -methoxybenzyloxyacetic acid 1 …”
Section: Resultsmentioning
confidence: 99%
“…To a solution of propargyl alcohol 1a (1.06 g, 4.48 mmol, 1.0 equiv) and (4-methoxy­benzyl­oxy)­acetic acid 2 (1.32 g, 6.72 mmol, 1.5 equiv) in CH 2 Cl 2 (20 mL) at 0 °C were added EDCI (1.29 g, 6.72 mmol, 1.5 equiv) and DMAP (109 mg, 0.896 mmol, 20 mol %). After stirring overnight at rt, the reaction mixture was hydrolyzed with a saturated aqueous solution of NH 4 Cl and diluted with EtOAc.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The resulting mixture was extracted with Et 2 O and the combined organic layers were washed with brine, dried over MgSO 4 , filtered and concentrated under reduced pressure. The residue was purified by flash chromatography (petroleum ether/Et 2 O = 90:10 to 70:30) to afford 1.10 g (94%) of 1l as a colorless oil; IR: To a solution of propargyl alcohol 1a (1.06 g, 4.48 mmol, 1.0 equiv) and (4-methoxybenzyloxy)acetic acid 243 (1.32 g, 6.72 mmol, 1.5 equiv) in CH 2 Cl 2 (20 mL) at 0 °C, were added EDCI(1.29 g, 6.72 mmol, 1.5 equiv) and DMAP (109 mg, 0.896 mmol, 20 mol %). After stirring overnight at rt, the reaction mixture was hydrolyzed with a saturated aqueous solution of NH 4 Cl and diluted with EtOAc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The decarboxylation products of ArOCH,CO,I are stable compounds and therefore we made independently 2,4-dichloro-a-iodoanisole (5) and found that it reacts not only with compound (3e) to afford compound (6) but also with other DIBs of type (3) providing access to mixed 2,4-dichlorophenoxymethyl aryloxyacetates (6) [Equation (6)]. The reaction can be extended to the preparation of 2,4dichlorophenoxy carboxylates, ' ( 7 ) [Equation ( 7)], by using simple DIBs.…”
mentioning
confidence: 99%